2020
DOI: 10.1101/2020.09.03.280719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Mental Health Paradox: Mental health was both a motivator and barrier to physical activity during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has impacted the mental health, physical activity, and sedentary behavior of citizens worldwide. Using an online survey with 1669 respondents, we sought to understand why and how by querying about perceived barriers and motivators to physical activity that changed because of the pandemic, and how those changes impacted mental health. Consistent with prior reports, our respondents were less physically active (aerobic activity, −11%, p <0.05; strength-based activity, −30%, p<0.01) and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…Our finding of significant associations between frequency of exercise, physical well-being and emotional well-being are consistent with other studies conducted during the pandemic that indicate lockdown experiences can disrupt and reduce exercise routines, which can have flow on effects for reducing physical and mental wellbeing (Brand et al, 2020;Ebrahimi et al, 2020;Galle et al, 2020;Marashi et al, 2020). Therefore, in any future pandemic scenario it would be useful for both broad scale interventions (e.g., public service announcements) and individual interventions conducted by mental health practitioners to promote healthy exercise and diet practices.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our finding of significant associations between frequency of exercise, physical well-being and emotional well-being are consistent with other studies conducted during the pandemic that indicate lockdown experiences can disrupt and reduce exercise routines, which can have flow on effects for reducing physical and mental wellbeing (Brand et al, 2020;Ebrahimi et al, 2020;Galle et al, 2020;Marashi et al, 2020). Therefore, in any future pandemic scenario it would be useful for both broad scale interventions (e.g., public service announcements) and individual interventions conducted by mental health practitioners to promote healthy exercise and diet practices.…”
Section: Discussionsupporting
confidence: 91%
“…Another reason is that some individuals may have increased exercise (with more time on their hands) that cancels out those exercising less. Consistent with other recent studies (Brand et al, 2020;Ebrahimi et al, 2020;Galle et al, 2020;Marashi et al, 2020), we found a link between frequency of exercise and well-being suggesting that keeping physically active can potentially act as a buffer for stress during lock-down.…”
Section: Emotional and Physical Well-being Exercise Concerns Sociasupporting
confidence: 92%
See 3 more Smart Citations